A political economy of the Poor People’s Campaign: From MLK and Polanyi to Trump - Callebert, Ralph; Soni, Raji Singh (Sikh Formations, 2018)
A stalemate has emerged in mainstream liberal/left responses to Trump. Many commentators prefer to see our predicament in terms of either class-based or identity politics. Vis-à-vis the influence of the Chicago school of economics and its structural adjustment schemes, we crosshatch MLK’s Poor People’s Campaign and Polanyi’s Great Transformation to envision overcoming this stalemate. King’s effort to radicalize the welfare state from below by linking struggles against poverty, racism, and imperialism shares Polanyi’s focus on the economy’s embeddedness in society. We underscore the importance of King’s and Polanyi’s visions for building a leftist coalition that does not divorce social from economic justice.
Keywords: Great Transformation, The (Book); KING, Martin Luther; Poor People's Campaign; TRUMP, Donald; embeddedness

In the market for humane rights - Inglis, Fred (Times Higher Education, 2018)
Keywords: Human rights; Moral Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); Rogan, Tim; austerity (economics); book review; cultural history; nonfiction

The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism - Crook, Paul (Australian Journal of Politics & History, 2018)
The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. By Tim Rogan (Princeton and Oxford, Princeton University Press, 2017), pp.263 + viii. AU$48.82 (hb). Available in Australia through Footprint Books.
Keywords: MORAL Economists: R.H. Tawney, Karl Polanyi, E.P. Thompson & the Critique of Capitalism, The (Book); POLANYI, Karl, 1886-1964 - political & social views; ROGAN, Tim; TAWNEY, R. H. (Richard Henry), 1880-1962; THOMPSON, E. P. (Edward Palmer), 1924-1993; book review; nonfiction; political attitudes

The Double Movement of the Landlord Class in Prewar Japan - Cohen, Mark (Journal of Japanese Studies, 2018)
The role of the landlord class in Japan's prewar economic and political development has been widely debated. Moving beyond conflicting arguments of landlords as semifeudal exploiters or as the linchpins of rural market development, more recent research has emphasized the nonmarket institutions, often inherited from the Tokugawa era, in which the contractual relations between landlords and tenants were embedded. However, this research has overemphasized the continuity of the rural economy. Rather than a smooth development, the historical trajectory of rural economic growth followed the "double movement" of capitalist development identified by the historian and economic anthropologist Karl Polanyi.
Keywords: Japan; Tokugawa Period, Japan, 1600-1868; capitalism; double movement; history; landlord-tenant relations

Karl Polanyi vs Friedrich von Hayek: The Socialist Calculation Debate and Beyond - Dale, Gareth (Hayek: A Collaborative Biography: Part XIV: Liberalism in the Classical Tradition: Orwell, Popper, Humboldt and Polanyi, 2018)
It is well known that Friedrich von Hayek’s The Road to Serfdom and Karl Polanyi’s The Great Transformation were written contemporaneously (between 1940 and 1943), that their authors propounded antithetical political ideologies (right-wing liberalism and left social democracy respectively), and that the two books revolve around a similar problematique: the causes of the collapse of liberal order in the interwar era. This chapter undertakes a detailed comparison of Hayek and Polanyi’s Weltanschauung (including ethics, economic analysis, and political perspectives). It reveals a chequered picture, in which diametrically opposed political views articulate with points of striking agreement in economic analysis. This helps to explain the manner in which certain Polanyian theses, notably on the ‘constructed’ market order and the ‘spontaneous’ social-movement response, appear to mirror those of Hayek.
Keywords: Great Transformation, The (Book); HAYEK, Friedrich A. von (Friedrich August), 1899-1992; Polanyi; constructed market order; history of economic thought; liberalism; methodology; socialist calculation debate